Understanding the perception on customer experience among tourists in Labuan / Andrea Sovilea Jaine - Jaine, Andrea Sovilea (2014)
The purpose of this particular research which is entitled "Understanding the Perception on Customer Experience among Tourists in Labuan" is to investigate the perception of consumer in regard with the three experience clues which are functional clue, humanism clue and mechanic clue. Labuan Federal Territory also known as Victoria Island is a popular getaway for a diverse range of tourists. Despite the rapid development in the tourism industry which brings about a wide business opportunity for the locals, the town still lacks accommodation to cater the demand of tourists especially during international events. Understanding tourists' perception on customer experience will enable local service providers how to better treat their customers and indirectly promotes business sustainability. Another purpose of this research is to identify the role of the main tourism service providers namely hotel, transportation provider and travel agency in contributing to the overall tourist experience and determine key aspects to increase customer satisfaction. This is because in a way or another tourists are likely to encounter at least one of the three aforementioned during their stay in Labuan. Therefore, the finding that the researcher collected through this particular research resulted in majority of the respondents having positive and satisfactory customer experience as tourists in Labuan. Each of the main tourism service providers play significant role to offer tourists a memorable experience staying in Labuan thus empowering them through the findings from this research is a privilege.